Effect of Wenxia Changfu Formula Combined With Cisplatin Reversing Non-Small Cell Lung Cancer Cell Adhesion-Mediated Drug Resistance - Wang, Meng-Ran; Chen, Rui-Jie; Zhao, Fang; Zhang, Hong-Hua; Bi, Qian-Yu; Zhang, Ya-Nan; Zhang, Yin-Qiang; Wu, Zhi-Chun; Ji, Xu-Ming (Frontiers in Pharmacology, 2020)
Non-small cell lung cancer (NSCLC), the major form of primary lung cancer, is a common cause of cancer-related death worldwide (Lee and Cheah, 2019). Cell adhesion-mediated drug resistance (CAM-DR), a form of chemotherapy resistance, has been reported to confer resistance to various chemotherapeutic agents. Integrin β1 signaling plays an important role in CAM-DR and has been proposed as a potential target for NSCLC (Baltes et al., 2020). Wenxia Changfu Formula (WCF) is a Traditional Chinese Compound Prescription for the intervention treatment of NSCLC combined with cisplatin (DDP). This study aims to investigate the effect and mechanism of WCF combined with DDP in reversing CAM-DR. Firstly, the chemical profile of WCF was characterized by UPLC/Q-TOF-MS analysis. A total of 237 compounds with mzCloud Best Match of greater than 70 were identified by using the online database mzCloud. Secondly, we established A549 three-dimensional(3D) cells cultured in vitro and nude mice xenografts models of the A549 cell line with Integrin β1 overexpression. In vitro, the cell viability, migration and adhesion were measured though MTT Assay, Wound Healing Assay and Cell Adhesion Assay, the Integrin β1 expression of the A549 cells was assessed through immunocytochemistry; In vitro, the transplanted tumor morphology and the colocalization of Integrin β1 and its ligands were tested by HE staining and immunofluorescence. As a result, we found that the combination effectively reduced cell viability, suppressed migration and adhesion, and downregulated the protein level of Integrin β1 in three-dimensional cultured A549 cells. And the combination of WCF with DDP significantly inhibited tumor growth, increased organelle vacuolations and decreased colocalization of Integrin β1 and its ligands including fibulin-2 and laminin. Taken together, our results confirm that the combination of WCF with DDP could reverse the lung cancer CAM-DR through the Integrin β1 signaling pathway.